Kekerabatan Bahasa Sumbawa dan Bahasa Madura: Kajian Linguistik Historis Komparatif - Febriani, Elya; Aliurridha, Aliurridha; Hidayat, `Rahmad (Ruang Kata, 2025)
This study aims to examine the kinship of Sumbawa and Madurese languages with three main objectives, namely are 1) identifying the sound correspondence between Sumbawa and Madurese languages, 2) determining the level of kinship between the two languages based on lexicostatistical calculations, and 3) calculating the separation time between Sumbawa and Madurese languages. This research is a descriptive study that applied quantitative and qualitative approaches. The data sources used consist of 200 basic Swadesh vocabularies. Data collection for Sumbawa and Madurese languages was carried out using interview techniques with native speakers of both languages. Data analysis uses lexicostatistics and glottochronology based on comparative historical linguistic studies described by Crowley & Bowern (2010) and Keraf (1996). The results of the study show that the correspondence of consonant sounds between the two languages tends to remain constant and unchanged, but vowel sounds experience irregular changes. There are also strong sounds that are maintained such as the sounds of mata, lima and empat gloss. The level of kinship of Sumbawa and Madurese language is 39.3% and is included in the family category. In addition, the Sumbawa and Madurese languages are estimated to have originated from the same proto-language around 1,962 to 2,154 years ago